Synthesis and Characterization of Wool Keratin/Hydroxyapatite/Alginate Composites (Journal of Fiber Bioengineering and Informatics, 2019)
Interests in HA/polymer composites for bone tissue engineering have escalated due to their excellentbiological response to damaged tissues. HA/polymer composites have been researched as potentialimplant in bone defects and voids. In this paper, HA was co-precipitated with two polymers includingwool keratin and alginate. By changing the concentrations of wool keratin solution, alginate solutionand Ca2+ and PO3−4 solution, the ratios of inorganic and organic phase were changed. The final resultshows that HA embedded in the organic phase well and HA nanoparticles grown on the surface of woolkeratin and linear alginate macromolecules formed cross-linking around Ca2+ of HA nanoparticles.
Keywords: Hydroxyapatite; Wool keratin; Alginate; Nanocomposite; Biomimetic